SOCIOECONOMIC ANALYSIS AND PARENTING PATTERNS ON THE INCIDENCE OF STUNTING IN TODDLERS IN AKABILURU DISTRICT, LIMA PULUH KOTA REGENCY: PARENTING PATTERNS ON THE INCIDENCE OF STUNTING - Umri, Zahriatil; Nursal, Dien Gusta Anggraini; Widoyo, Ratno (STIKes Mandala Waluya Kendari, 2025)
Background: Akabiluru Subdistrict was chosen as the research location because of the high prevalence of stunting among toddlers and its correlation with various socioeconomic factors and parenting patterns at the household level. This study aims to analyze the influence of socioeconomic factors and parenting patterns on the incidence of stunting among toddlers. Methods: This study used a mixed-method design with quantitative and qualitative approaches. The quantitative stage used a case-control study with a sample of 94 cases and 94 controls. The qualitative phase used a sequential explanatory model through FGDs with selected informants to explore mothers' perceptions, cultural factors, family roles, and access to information, which were thematically analyzed to support the quantitative findings. Results: The results of this study found that maternal education, exclusive breastfeeding, and basic immunization status were significantly associated with stunting, with exclusive breastfeeding being the dominant factor. Qualitative findings showed that exclusive breastfeeding practices were influenced by maternal perceptions, cultural factors, family roles, and access to information. Conclusion: This study shows that exclusive breastfeeding is a dominant factor associated with stunting in toddlers in Akabiluru District.